A case report of successful treatment of secondary aortoenteric fistula complicated with gastrointestinal bleeding and retroperitoneal abscess in an elderly patient. Issue 24 (June 2018) - Jiang, Chunyan; Chen, Xueming; Li, Jianshe; Li, Hongwei
Abstract: Rationale: The treatment of secondary aortoenteric fistula (SAEF) involves maintaining hemodynamic stability, infection control, revascularization, and surgical repair. Conventional open repair is associated with high mortality, whereas endovascular stent-graft repair is associated with recurrent infection or bleeding. Patient concerns: We report the case of an 85-year-old man with SAEF who presented with gastrointestinal bleeding and retroperitoneal abscess. Diagnoses: He was misdiagnosed for 5 months. SAEF was eventually diagnosed by CT and gastroduodenoscopy. Interventions: The patient underwent hybrid open surgery: extraanatomic left axillofemoral bypass graft reconstruction, exploratory laparotomy, aortic stent graft excision, infrarenal abdominal aortic suture, left common iliac artery ligation, extensive surgical debridement, and retroperitoneal abscess resolution and drainage, along with duodenal defect repair and jejunal feeding tube placement. Outcomes: He survived the complicated surgery and several life-threatening complications with multidisciplinary management. He has kept well for 15 months. Lessons: Elderly SAEF patients can undergo open repair when circumstances permit, but multidisciplinary management is crucial.